Stories from the Serat Centhini : understanding the Javanese journey of life - Santoso, Suwito; Pringgoharjono, Kestity, 1974-; Siregar, Fendi, 1949- (Singapore : Marshall Cavendish Editions, 2013)
This book is based on The Centhini Story, the condensed, English-language translation of the original 12-volume Serat Centhini, one of Indonesia's oldest surviving manuscripts, dating back to 1814. It tells of the flight and reunion of three royal children from the Kingdom of Giri when their father went to war.
Keywords: Javanese literature; Java (Indonesia) -- Social life and customs -- Fiction